Rehabilitation Therapy Doses Are Low After Stroke and Predicted by Clinical Factors. Issue 3 (3rd February 2023) - Young, Brittany M.; Holman, E. Alison; Cramer, Steven C.
Abstract : Background: Stroke is a leading cause of long-term disability. Greater rehabilitation therapy after stroke is known to improve functional outcomes. This study examined therapy doses during the first year of stroke recovery and identified factors that predict rehabilitation therapy dose. Methods: Adults with new radiologically confirmed stroke were enrolled 2 to 10 days after stroke onset at 28 acute care hospitals across the United States. Following an initial assessment during acute hospitalization, the number of physical therapy, occupational therapy, and speech therapy sessions were determined at visits occurring 3, 6, and 12 months following stroke. Negative binomial regression examined whether clinical and demographic factors were associated with therapy counts. False discovery rate was used to correct for multiple comparisons. Results: Of 763 patients enrolled during acute stroke admission, 510 were available for follow-up. Therapy counts were low overall, with most therapy delivered within the first 3 months; 35.0% of patients received no physical therapy; 48.8%, no occupational therapy, and 61.7%, no speech therapy. Discharge destination was significantly related to cumulative therapy; the percentage of patients discharged to an inpatient rehabilitation facility varied across sites, from 0% to 71%. Most demographic factors did not predict therapy dose, although Hispanic patients received a lower cumulative amount of physical therapy and occupational therapy. Acutely, the severity of clinical factors (grip strength and National Institutes of Health Stroke Scale score, as well as National Institutes of Health Stroke Scale subscores for aphasia and neglect) predicted higher subsequent therapy doses. Measures of impairment and function (Fugl-Meyer, modified Rankin Scale, and Stroke Impact Scale Activities of Daily Living) assessed 3 months after stroke also predicted subsequent cumulative therapy doses. Conclusions: Rehabilitative therapy doses during the first year poststroke are low in the United States. This is the first US-wide study to demonstrate that behavioral deficits predict therapy dose, with patients having more severe deficits receiving higher doses. Findings suggest directions for identifying groups at risk of receiving disproportionately low rehabilitation doses.